Phonetic Transcription Training Improves Adults' Explicit Phonemic Awareness: Evidence From Undergraduate Students. (November 2017) - Werfel, Krystal L.
The purpose of this study was to evaluate the effects of phonetic transcription training on the explicit phonemic awareness of adults. Fifty undergraduate students enrolled in a phonetic transcription course and 107 control undergraduate students completed a paper-and-pencil measure of explicit phonemic awareness on the first and last days of class. Performance was analyzed for overall accuracy, as well as accuracy on easy-to-segment and hard-to-segment words. A MANCOVA revealed a main effect of group on each dependent variable. In addition, intervention-group pretest and posttest scores were not related. Thus, phonetic transcription training appears to be an effective method of increasing explicit phonemic awareness in adults, and initial skill level is not related to gains as a result of phonetic transcription training.